O programa nacional de alimentação escolar (PNAE): um estudo da efetividade no cumprimento das ações para fortalecer a agricultura familiar - Tugoz, Jamila El (2015)
The Universal Declaration of Human Rights establishes that the State must respect, protect and facilitate the action of individuals and communities aiming to feed themselves in dignity, quality of life and citizenship. Brazil has developed state policies aimed at this purpose, among them, the National School Feeding Programme (PNAE), which still faces obstacles that hinder its application fully effectively. In this context, the aim of this study is to evaluate the effectiveness of PNAE in carrying out actions to strengthen family farming (AF). For this, the stages of work were established the following specific objectives: to describe National School Feeding Programme (PNAE) and the sustainable development of family farming; to identify perception, behavior and environmental education; to verify financial viability of the production of organic food for school meals; promoting sustainable development of family farming; identification of obstacles to the insertion of the Family Farmer (AF) in the National School Feeding Programme (PNAE) through access to the institutional market locally. This study is characterized as a bibliographical, documentary, descriptive and exploratory, quantitative and qualitative research. Data collection was through instruments like Vapercom, questionnaires and structured interviews. The study shows that PNAE and sustainable development have received attention from universities, revealed the diversity of study and graduate programs involved with the theme. However, for the students still need to step up investment, both by government as part of the business community, in awareness campaigns on the subject. Overall, it is essential the continuity and expansion of the PNAE to strengthen food security and development policy of the local family farms, generating jobs and income and playing an important role as an instrument of sustainability in its different dimensions. However, to access and continuity of farmers in PNAE, all these questions that guide or impact the negotiations between Government and farmers, should be discussed and reassessed, seeking measures to enable progress to the sustainable development of local family farmers